Meningkatan Keterampilan Proses Sains melalui Metode Pembelajaran Eksperimen - Kamila Mahabatillah (Jurnal Riset Pendidikan Guru Paud, 2022)
Abstract. The problem in this study has not been seen in children's science process skills. The teacher applies a learning process that is based on student worksheets and the learning process is still teacher-centered. This causes children to be bored and have difficulty in obtaining new information, resulting in children's scientific process skills not developing properly. The purpose of this study was to determine: (1) Description of children's science process skills before applying the experimental learning method to the introduction of natural phenomena (2) Description of the implementation of natural symptom recognition activities through experimental learning methods in improving children's science process skills (3) Finding the results of science process abilities after applying the experimental learning method to the introduction of natural phenomena, (4) Identifying the effect of the experimental learning method in increasing children's science process skills. This study uses a quantitative research type of quasi-experimental research. The measurement of this study uses a rating scale while in testing the truth of the hypothesis using theformula, the Independent T Test value of sig. (2-tailed) of 0.001 <0.05, Ho rejected and Ha accepted. In accordance with the criteria for testing the hypothesis, namely sig. (2-tailed) < 0.05 so it can be stated that there is a significant difference in results between the experimental class and the control class on science process skills in recognizing rain natural phenomena Abstrak. Permasalahan dalam penelitian ini belum terlihatnya keterampilan proses sains anak. Guru menerapkan proses pembalajaran yang terpacu pada lembar kerja siswa serta dalam proses pembelarajan masih berpusat pada guru. Hal ini menyebabkan anak bosan dan kesulitan anak dalam memperolah informasi baru, mengakibatkan keterampilan proses sains anak belum berkembang dengan baik. Tujuan penelitian ini untuk mengetahui : (1) Gambaran keterampilan proses sains anak sebelum diterapkan metode pembelajaran eksperimen pada pengenalan gejala alam (2) Gambaran pelaksanan kegiatan pengenalan gejala alam melalui metode pembelajaran eksperimen dalam meningkatkan keterampilan proses sains anak (3) Menemukan hasil kemampuan proses sains anak sesudah diterapkan metode pembelajaran eksperimen pada pengenalan gejala alam, (4) Mengidentifikasi pengaruh metode pembelajaran eksperimen dalam meningkat keterampilan proses sains anak. Penelitian ini menggunakan penelitian kuantitatif jenis penelitian quasi eksperimen. Pengukuran penelitian ini menggunakan rating scale adapun dalam menguji kebenaran dari hipotesis menggunakan rumus Uji Independent T nilai sig. (2-tailed) sebesar 0,001 < 0,05, maka Ho ditolak dan Ha diterima. Sesuai dengan kriteria uji hipotesis yaitu sig. (2-tailed) < 0,05 sehingga dapat dinyatakan bahwa terdapat perbedaan hasil yang signifikan antara kelas eksperimen dengan kelas kontrol pada keterampilan proses sains kegiatan pengenalan gejala alam hujan.